ANALISIS RASIO LANCAR RUMAH SAKIT X - Marsdenia Marsdenia (Jurnal Vokasi Indonesia, 2013)
ABSTRACT – Increasing the efficiency of hospital management sustainability is an ongoing financialmanagement guidelines that absolutely must be adopted by any hospital. This study aims at obtaininginformation about the components that contribute to the fluctuations of the current ratio Hospital X between2000, 2001 and 2002. This study used quantitative and qualitative approaches, with the primary data source(in-depth interviews to the relevant parties ie Hospital Director, Chief Financial Officer and Vice DirectorAdiministrasi Finance) and the secondary data source include financial statements. The research shows thatRS X’s current ratio are still in a normal range except in the year of 2001 was below the standard (1.42). Themore sensitive ratio, Acid Test Ratio, is still in normal range in the year of 2000, but in the year of 2001, and2002, the ratios are in the lowest bend of the normal range. Cash Ratios for many years are also in the lowestbend except for the year of 2000, Receivable turn over ratios for the last three years go smaller showing thatreceivables took longer time to collect, the normal range for receivable turn over is 14 up to 20 days. Inventoryturn over ratios are below the standard range (24-32 times per year), the average inventory held in warehouseAnalisis Rasio Lancar Rumah Sakit XMarsdeniaVolume 1, Nomor 2, pp 61-8362is between 16 up to 21 days. The value of current ratio is got from comparison between current assets andcurrent liabilities. Nominally, RS X’s current ratio in 2002 is in the state bend, namely, 1.5 – 2.00, in the realterm, the ratio shows on contradictory pictures. The reasons are a) Guaranteed Receivables are valued abovethe normal practice (overstated) b) overstated of Non Guaranteed receivables/Personal Receivables.Based on this research, the author thinks that there are some rooms for RS X’s management to fittheir current ratio problem. There are several suggestions that the management can adopt, namely controllingcash outflow and cash inflow, reevaluating receivables policy, reforming the supply of inventories (medicine)procedures.Keywords: Current ratio, cash, patient receivables, inventory, current liabilities.